From poverty reduction to poverty relief: impact of non-farm income in Integrated Agriculture Development Area (IADA) Samarahan, Sarawak, Malaysia - Nor Diana Mohd Idris; Chamhuri Siwar (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Eradication of poverty is the main agenda of the country since independence (1957) and a main thrust of the New Economic Policy (NEP) when it was introduced in 1970. As a result, Malaysia has been able to achieve the goal of reducing poverty, from 52.4% in 1970 to 1.7% in the year 2012. This study examines the impact of non-farm income on poverty and its effect on the time taken to attain relief from poverty. Face-to-face interviews with 220 households of farmers in the Area of Integrated Agricultural Development (IADA) in Samarahan, Sarawak were conducted from December 2005 to February 2006. The objective was to investigate the effect of non-farm income on poverty and to measure the length of time out taken for farmers to emerge out of poverty. The analysis on poverty measurement was done using FGT indices as proposed by Foster, Greer and Thorbecke; and the index introduced by Murdoch was also employed in this study. The results showed that non-farm income reduced poverty by 47.06%, while the poverty gap declined by 58.67% and the intensity of poverty (severity of poverty) decreased by 80.69%. The time required to break away from poverty for poor and hard-core poor farmer households with nonfarm income were 8.16 years and 6.51 years, respectively compared with 11.49 years for poor and 8.67 years for hard-core poor farmers without non-farm income. This proved that non-farm income sources were essential in reducing the transition period from poverty reduction to poverty relief for farmers in the IADA .